Physical and Mechanical Properties of White Teak Wood (Gmelina Arborea) from Ampana, Poso, Central Sulawesi Based on the Position of the Wood in the Trunk - Erniwati; Ariyanti; Mutmainnah; Imran Rachman (Postgraduate, University of Mataram, 2025)
The basic properties of this wood are also greatly influenced by factors within the wood and external factors such as where the wood grows. This research was conducted from June to September 2024 at the Soil Science Laboratory, Faculty of Agriculture, and the Mechanical Engineering Laboratory, Faculty of Engineering, Tadulako University to determine the physical and mechanical properties of white teak wood from Ampana, Poso, Central Sulawesi. The design method used in this study is RAL Factorial with two factors, namely: Factor A variation of the axial direction (base, middle, tip) and, Factor B variation of the radial direction (near the heart, middle, near the skin), so that there are 9 treatments and each treatment is repeated 5 times. The results of the study showed that both physical and mechanical properties were influenced by the position of the wood in the trunk where the position of the wood in the trunk affects the physical and mechanical properties of the wood studied. Based on the MOE value, the white teak wood studied is included in the strength class V. Based on the MOR value and compressive strength parallel to the grain, the wood studied is included in the strength class III which can be used as raw material for furniture and light construction.